The Relationship Between Nutritional Status, Dietary Patterns, and Premenstrual Syndrome in Adolescent Girls - Sheilla, Evi; Patria, Armen; Puteri, Hidayatusy Syukrina (Inspirasi Foundation, 2026)
Introduction: Premenstrual syndrome (PMS) is a common condition among adolescent girls that causes physical and psychological discomfort and may interfere with daily activities. Nutritional status and dietary habits, particularly the consumption of fast food and junk food, are considered important factors associated with the occurrence of PMS. Changes in adolescents’ eating patterns toward high-calorie, high-fat, and low-fiber foods may increase the risk of nutritional imbalance and PMS symptoms. Therefore, this study aims to examine the relationship between nutritional status, fast food and junk food consumption, and premenstrual syndrome among adolescent girls. Objective: Nutritional status is a state of balance between nutrient intake and needs, expressed using a Z-score value based on BMI/Age. The purpose of this study was to determine the relationship between overweight status of fast food and junk food with premenstrual syndrome (PMS) in female adolescents at SMA Negeri 1 Sukoharjo in 2025. Method: The method used in this study was quantitative with a cross sectional approach which was carried out in May 2025 with a total of 87 female adolescent students, taken through purposive sampling, the research sample was taken according to the inclusion and exclusion criteria. The research instrument used the SPAF questionnaire consisting of 10 questions. Result: Data analysis using univariate analysis with frequency distribution and bivariate analysis with spearman’s rank correlation analysis the results of the study showed that the sig value was 0,021 < p-value 0,05, which means that there is a significant relationship between nutritional status and the incidence of premenstrual syndrome (PMS) in female adolescents at SMA Negeri 1 Sukoharjo in 2025. Based on the results 0f the study, it was found that the sig value was 0,034 < p-value 0,05, which means that there is a significant relationship between junk food and the incidence of premenstrual syndrome (PMS) in female adolescents at SMA Negeri 1 Sukoharjo in 2025. Conclusion: , it was found that the sig value was 0,010 < p-value 0,05, which means that there is a significant relationship between fast food and the incidence of premenstrual syndrome (PMS) in female adolescents at SMA Negeri 1 Sukoharjo in 2025.